Analisis Yuridis Notaris Sebagai Pihak Pelapor Dalam Pencegahan Dan Pemberantasan Tindak Pidana Pencucian Uang (Studi Pasal 3 huruf (b) PP RI Nomor 43 Tahun 2015 Tentang Pihak Pelapor Dalam Pencegahan dan Pemberantasan Tintak Pidana Pencucian Uang) - Reynaldi Putra Rosihan (Universitas Islam Sumatera Utara, 2020)
The issuance of Government Regulation Number 43 of 2015 concerning Reporting Parties in the Prevention and Eradication of the Crime of Money Laundering, as in Article 3 of this Government Regulation affirms that a notary is the reporting party for the alleged crime of money laundering on the deed he has made. If this reporting obligation is not carried out by the notary and the deed that has been made by him is related to the crime of money laundering, according to the provisions of Article 5 of Law Number 8 Year 2010 concerning the Prevention and Eradication of the Crime of Money Laundering, he will be subject to the criminal sanctions and fines. In this regard, it is necessary to examine more deeply the consideration of including a notary as the reporting party in the prevention and eradication of the crime of money laundering against the deed he made.Notaries are involved as reporting parties in the prevention and eradication of the crime of money laundering because the prevention and eradication of the crime of money laundering in Indonesia has not been maximal with the increasingly sophisticated mode of money laundering because it utilizes the notary profession as a means of money laundering by the perpetrators to smoothen their actions against money which is obtained from the proceeds of crime and the involvement of a notary. Reporting implementation mechanism by a notary as a party to report money laundering crimes, First, the reporting party is obliged to apply the principle of recognizing service users, then to carry out the reporting to the PPATK, the notary is obliged to register and fill in the report by assigning a reporting officer, registering through the Gathering Reports and Information Processing System (GRIPS) application.Keywords : Notary, Prevention, Eradication, Money Laundering.